Criteria for assessing the best interests of the child in procedures for the protection of children's rights - Mihajlović, Ljubica (Glasnik Advokatske komore Vojvodine, 2023)
The principle of the best interest of the child is one of the four basic principles the children's rights protection system is based under the auspices of the United Nations and the Convention on the Rights of the Child. As such, it represents a general principle, a term to which legal practitioners attach a specific meaning in each specific case. The Family Law of the RS, as well as the Convention on the Rights of the Child, do not contain a definition of this principle, which leaves a wide space for assessing what the best interest of the child in concreto represents. In this regard, general comment no. 14(2013) of the Committee on the Rights of the Child on the best interests of the child, sets objective criteria as guidelines that all decision-makers concerning children should apply. In this sense, the subject of the paper will be an overview of the dominant positions of judicial practice in the legal system of the Republic of Serbia regarding the criteria for assessing the best interests of the child.
Keywords: the best interest principle, objective criteria, judicial proceedings